PENGGUNAAN MEDIA CHEMO-EDUTAINMENT UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA PADA MATERI SEL ELEKTROLISIS DI SMAN 1 PRAYA BARAT DAYA - Ulfa Rohimah; Muntari Muntari; Yayuk Andayani; Lalu Rudyat Telly Savalas (Chemistry Education Practice, 2026)
The low level of students’ learning activities and achievement in topics on electrolysis cells remains a challenge in chemistry learning due to the abstract nature of the concepts involved. This study aimed to improve students’ learning activities and achievement through the use of a Chemo-Edutainment medium, namely the Chemopoly (Chemistry Monopoly) game, on the topic of electrolytic cells at SMAN 1 Praya Barat Daya. This research employed a Classroom Action Research (CAR) design conducted in two cycles. Data were collected through observation, tests, and documentation. Students’ learning activities were assessed using observation sheets, while learning achievement was measured through achievement tests administered at the end of each cycle. The results showed that the implementation of the Chemo-Edutainment medium significantly improved both students’ learning activities and achievement. The average learning activity score increased from 54% in Cycle I to 79% in Cycle II. Similarly, the percentage of students achieving learning mastery improved from 45% in Cycle I to 75% in Cycle II. These findings indicate that the Chemopoly-based Chemo-Edutainment medium is effective in enhancing students’ learning activities and academic achievement in learning about electrolysis cells.